Establishing a Profession through Boundary Drawing: Defining Criminology’s Autonomy Vis-À-Vis Six Competing Disciplines - Dooley, Brendan D. (American journal of criminal justice, 2022)
Criminology as an independent profession established itself just over a half century ago. An analysis of oral histories collected with seventeen leading scholars in criminology reveal how the profession has worked to establish institutional legitimacy over that time. Extending a thesis of boundary drawing (Gieryn, 1999) the present effort first briefly traces the field’s emancipation from its former intellectual home in sociology. Second, third, and fourth criminology has established a border with economics, public health, and biology while permitting "home disciplines" to continue to inform its formation. Fifth and sixth,it has distinguished itself internally from both Justice Studies and Law and Society. The field has worked to establish separation through crafting an interdisciplinary framing of its approach to the subject of crime that is influenced by but not dependent upon its more established peers. Criminology has made unique contributions to the development of methods and policy. While the emergent field has established a measure of separation from more established academic enterprises, several respondents expressed a lack of paradigmatic markers of theoretical and methodological consensus that carry potential professional costs if left unaddressed. Lessons can be drawn from the frustrations and promise of establishing multidisciplinary, policy-centric fields.